Rape at the Opera - Cormier, Margaret (University of Michigan Press, 2023)
The most-performed operas today were written at least a hundred years ago and carry some outdated and deeply problematic ideas. When performed uncritically, the misogyny, racism, and other ideologies present in many of these works clash with modern sensibilities. In Rape at the Opera, Margaret Cormier argues that production and performance are vital elements of opera, and that contemporary opera practitioners not only interpret but create operatic works when they put them onstage. Where some directors explicitly respond to contemporary dialogues about sexual violence, others utilize sexual violence as a surefire way to titillate, to shock, and to generate press for a new production.